A Riesz Representation Theorem for the Space of Henstock Integrable Vector-Valued Functions. (17th May 2018) - Pérez Becerra, Tomás; Escamilla Reyna, Juan Alberto; Rodríguez Tzompantzi, Daniela; Oliveros Oliveros, Jose Jacobo; Aye, Khaing Khaing
Abstract : Using a bounded bilinear operator, we define the Henstock-Stieltjes integral for vector-valued functions; we prove some integration by parts theorems for Henstock integral and a Riesz-type theorem which provides an alternative proof of the representation theorem for real functions proved by Alexiewicz.